2021
DOI: 10.1097/md.0000000000026506
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of inflammatory and nutritional markers for hepatocellular carcinoma

Abstract: Background: It is well known that the prognosis of cancer patients after tumor resection is closely related to the patient's autoimmune ability and nutritional status. A large number of studies have shown that the neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and Onodera's prognostic nutritional index (OPNI) are signi cantly correlated with the prognosis of various tumors. In this study, we analyzed the prognostic value of NLR, PLR and OPNI for hepatocellular carcinoma (HCC) for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Elevated PLR is associated with increased all-cause mortality in different conditions [120], is a prognostic marker in many cancers [121] and is also associated with nutritional status [122]. As a marker of nutrition, PLR was significantly correlated with PNI and BMI in pancreatic cancer patients [87]; along with NLR was significantly associated with PNI in hepatocellular carcinoma [123]. PLR is also associated with haemoglobin and post-op complications in colorectal cancer patients affecting morbidity rates [124].…”
Section: Inflammation Scoresmentioning
confidence: 99%
“…Elevated PLR is associated with increased all-cause mortality in different conditions [120], is a prognostic marker in many cancers [121] and is also associated with nutritional status [122]. As a marker of nutrition, PLR was significantly correlated with PNI and BMI in pancreatic cancer patients [87]; along with NLR was significantly associated with PNI in hepatocellular carcinoma [123]. PLR is also associated with haemoglobin and post-op complications in colorectal cancer patients affecting morbidity rates [124].…”
Section: Inflammation Scoresmentioning
confidence: 99%
“…[23] Recently, the association of gallbladder wall thickness with hepatic decompensation has been explored in some cross-sectional studies. [7,[24][25][26] Elkerdawy et al [7] found that gallbladder wall thickness was associated with the presence of esophageal varices in patients with cirrhosis. Mohammadi et al [25] demonstrated that thickened gallbladder wall was highly predictive for the presence of ascites in liver cirrhosis.…”
Section: Journal Of Translational Internal Medicine / Aopmentioning
confidence: 99%
“…Liver cancer is one of the leading causes of cancer death worldwide (Sun et al, 2013;Zhao et al, 2015;Kido et al, 2020). Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer (Ahn et al, 2018;Xu et al, 2021). Numerous studies have recently revealed that DUXAP10 was overexpressed in HCC cell lines (including Hep3B, HepG2, SMMC7721, HuH7, MHCC-97L, MHCC-97H, HCC-LM, and SK-Hep-1 cells) and tissues (Zhu et al, 2018;Han et al, 2019;Sun et al, 2019).…”
Section: Liver Cancermentioning
confidence: 99%